Communication Needs for Individuals With Rare Diseases Within and Around the Healthcare System of Northern Ireland - Ashleen L. Crowe; Amy Jayne McKnight; Helen McAneney (Frontiers Media S.A., 2019)
Objective: By definition a rare disease affects fewer than 1 in 2,000 people but collectively 1 in 17 people are affected at some time in their lives. Rare disease patients often describe feeling isolated and unsupported. The needs of individuals living with rare disease(s) are not well met globally and have not been specifically explored in Northern Ireland.Methods: An online survey was conducted in spring of 2017, focused on information and communication needs, to identify overarching themes. Databases were searched to place responses in an international context.Results: There were 240 survey respondents with four overarching themes identified: sources of information; medical care; rare disease community; and public awareness. Thirty relevant papers resulted from the literature search. A coordinated and transparent approach for improved medical care is needed where researchers, practitioners, and policy makers work with patients, carers, and rare disease advocates to ensure a fully considered rare disease strategy is implemented. In line with that developed by many other countries, a physical or virtual Northern Ireland reference network or center of excellence for rare diseases would provide an important strategic link. Sustainable funding, resources for rare disease charities, and more cross-border working would help build a local rare disease community. Major challenges highlighted include finding the right health and social care information. The internet was the most regularly accessed, and perceived as the easiest way, to source information on rare disease. Improved signposting to accredited information, ideally by the creation of a locally relevant online information hub, a local rare disease registry that can integrate with international systems, a local rare disease coordinator, and improving public awareness are urgent needs.Conclusions: Aligned to internationally reported outcomes, practical issues for future development based on the voices of individuals living, and working with a rare condition are described. It is essential that ongoing research evaluates changes to ensure that the best possible structures and mechanisms are put in place to improve communication and information systems for those affected by a rare condition(s).